PENERAPAN METODE PEMBELAJARAN TUTOR SEBAYA UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI SMA NEGERI 9 PONTIANAK - Rosanti, Diana (Universitas Tanjungpura, 2018)
AbstractÂ This study aims to determine the improvement of student activity and learning outcomes in the system of linier equations of three variables using peer tutoring methods. Form of research is classroom action research consists of two cycles. Each cycle stage consists of planning, implementation, observation and reflection. Data collection was obtained by direct observation and test. Subject are students of class X (Sosial science) 1 SMAN 9 Pontianak. Based on the results of research, it can be concluded that learning by peer tutoring methods can improve the activity and learning outcomes of students. This is marked by the increase of student activity average starting from cycle I of 2.96 (good category) to 3.51 (very good category) in cycle II with percentage increase of 58.33%. There is an increase because the tutor understands the material and has a good emotional level towards his friend.Â In line with the ability possessed by the tutor and the ability of the teacher in managing the learning, there is a significant increase of the test results given. At the pre cycle the percentage of students' completeness of 26.32% increased by 28.95% to 55.26% in cycle I. Similarly in cycle II there was an increase in learning outcomes by 31.58% from 55.25% in cycle I to 86.84% in cycle II. In accordance with the research indicator that the success of this study is seen from 80% of students complete with minimal standart is 75, so this research is said to be successful and stopped in cycle II.Â Keywords : Peer Tutoring Methods, Activity, Learning Outcomes